KAJIAN SOSIOPRAGMATIK TINDAK TUTUR ASERTIF DALAM ADEGAN LIMBUKAN - S., Suratno (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2015)
This study aims to describe the verbal interaction behavior in the dialogue of two female panakawanin wayang purwa performance by Ki Purbo Asmoro. The analysis is focused on (1) identifying thekind of assertive speech act, deciding the dominant speech act, (2) conveying the speechimplicature and describing the implementation of assertive speech act in relation to Griceâ€™s cooperative principles. The findings include once, the assertive speech act consists of: a. informing, b.telling, c. thinking, d. convincing, e. responding, f. ensuring, g. confirming, h. estimating, i.remembering, and j. implicating. The dominant assertive speech act from all the kinds is â€œinformingâ€ speech act. Secondly, based on the dominant conventional implicature and thirdly, there isintentionally infraction of Griceâ€™s cooperative principles in order to get the audiencesâ€™ sympathy aswell as to make them happy, and also to convey the explicit speech and to fulfill the politenessprinciples.Keywords: assertive speech act, implicature, and implementation.